1958
DOI: 10.1083/jcb.4.4.459
|View full text |Cite
|
Sign up to set email alerts
|

The Fine Structure of the Rod-Bipolar Cell Synapse in the Retina of the Albino Rat

Abstract: The fine structure of the rod-bipolar synapse is described and illustrated. Each rod spherule possesses a large, single, oval or elongate mitochondrion approximately 0.5 X 2.0 microns. Surrounding the mitochondrion are elements of agranular endoplasmic reticulum. The bipolar dendrite projects into the lower pole of the spherule and usually terminates in two lobes separated by a cleft. The plasma membranes appear dense and thicker in the region of the synapse. In the rod spherule cytoplasm, contiguous with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0
2

Year Published

1960
1960
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(47 citation statements)
references
References 14 publications
2
43
0
2
Order By: Relevance
“…In general terms, the rod synaptic base, that is the rod spherical, is one of the largest synapses in the central nervous system and may be characterized as a bulbar ending containing a bilobular invagination resembling two juxtaposed footballs. Ladman (1958) has further described the rod spherical as containing a single large mitochondria located above the bilobular invagination, although other authors have not specifically confirmed this observation. Other elements within the cytoplasm of the spherical are granular and innerplasmic reticulum and, of course, synaptic vesicles.…”
Section: Intrastructural Morphology Cellular Morphologymentioning
confidence: 79%
See 1 more Smart Citation
“…In general terms, the rod synaptic base, that is the rod spherical, is one of the largest synapses in the central nervous system and may be characterized as a bulbar ending containing a bilobular invagination resembling two juxtaposed footballs. Ladman (1958) has further described the rod spherical as containing a single large mitochondria located above the bilobular invagination, although other authors have not specifically confirmed this observation. Other elements within the cytoplasm of the spherical are granular and innerplasmic reticulum and, of course, synaptic vesicles.…”
Section: Intrastructural Morphology Cellular Morphologymentioning
confidence: 79%
“…Following the elegant descriptions of De Roberts and Franchi (1956), Gray and Pease (1971), Ladman (1958), and Leure-duPree (1974), the present report will concentrate upon the synaptic base of the rod receptor. This concentration is not necessarily a denial of cone receptors within the rat's retina, but simply a concession to available data.…”
Section: Intrastructural Morphology Cellular Morphologymentioning
confidence: 99%
“…Mitochondria are distributed throughout the inner segment and synaptic terminal. 6,9,11,35 The different architectures of rod and cone outer segments represent a major distinctive feature of the two photoreceptor cell types. Cones are conical shaped cells and their outer segments are generally shorter than rods.…”
Section: Structure and Functions Of Photoreceptorsmentioning
confidence: 99%
“…The arciform density, which is thought to anchor ribbons to the presynaptic membrane (Ladman, 1958), is absent in the majority of nrc photoreceptor terminals (Allwardt et al, 2001). The nrc synaptic malformities are associated with blindness and defective synaptic transmission between cones and bipolar cells characterized by pronounced asynchronous oscillations in the electroretinogram response (Allwardt et al, 2001;Van Epps et al, 2001).…”
Section: Introductionmentioning
confidence: 99%